Työhyvinvoinnin edistäminen kuntien hr-vastuullisten puheissa - Viitala, Riitta; Lehto, Kirsi (Focus Localis ry., 2019)
Well-being at work is a holistic phenomenon. It consists of the sum of factors related to the person (physical, psychological and social well-being) and the working environment and work community (atmosphere and management). During the ongoing reforms in municipalities, the importance of managing well-being at work of their employees is highlighted in a new way. However, the overall development and priorities of managing well-being at work, depends largely on the perceptions of managers and HR professionals. This article examines municipal HR professionals’ perceptions about level of management of wellbeing at work and related development needs in their organisations. The data includes interviews with ten professionals, who are responsible for management of employee well-being in municipalities. A content analysis method was used to analyse the data. The findings indicate that there is notable variation in HR professionals' perceptions of employee well-being and its development needs. The variation manifested for example in holistic vs. scattered perceptions, long-term vs. short-term focus, and different emphasis concerning the targets, methods and roles of responsible actors. The paper contributes to the theoretical academic discussions on holistic views of employee well-being and its management, and on HR professionals' roles in this. From the practical point of view, this paper proposes that a more systematic management approach to well-being of personnel is needed.
Keywords: fi=Johtaminen ja organisaatiot|en=Management and Organization|